A Focus on Methodology: A Mixed-Methods Approach to Conduct a Comprehensive Evaluation of the Need for One Health Education for Medical and Veterinary Students in the Context of COVID-19. (February 2022) - Roopnarine, Rohini R; Boeren, Ellen
Background: The collaboration of health professionals across the interface of human, animal and environmental health, as embodied by the One Health concept (OH), is increasingly recognised as crucial for tackling diseases such as Ebola and COVID-19. This study was conducted prior to the COVID-19 pandemic, but in light of the current pandemic, the outcomes of this study highlight the need for educating Medical (MD) and Veterinary (DVM) students on the principles of OH. The purpose of this study was to determine the need for Interprofessional Education (IPE) initiatives that would familiarise MD and DVM students with the principles of OH, crucial to dissolving the siloes that have historically deterred collaboration. Method: We used a sequential explanatory Methods Research (MMR) approach design to evaluate the readiness of 428 students consisting of MD, DVM and dual degree Master of Public Health (MPH) students (MD/MPH, DVM/MPH) for IPE, as well as to obtain faculty perspectives across these disciplines, on the need for curricula inclusion of IPE and OH. Two methods of data collection were employed: A survey and 2 focus groups interviews. Results: The use of an MMR approach allowed us to comprehensively evaluate the need for OH education through the lenses of the students and faculty using a joint display that facilitated data integration and evaluation. Overall, the dual degree students had the greatest readiness for IPE, and MD students the lowest level of readiness for shared learning. The dual degree students had the most accurate understanding of OH competencies that consider the impacts of climate change, food security, antimicrobial resistance, health policy formation and zoonoses occurrence on human health. Themes derived from the focus group interviews revealed that faculty perceived OH education as crucial for preparing MD and DVM students for practice. Conclusion: The comprehensive assessment of the student and faculty perspectives, obtained using an MMR approach, illustrated that the incorporation of OH competencies within the MD and DVM curricula are crucial for preparing students for practice in the global environment. The dual degree pathway provides insight into how OH can be successfully incorporated within the curricula of these programmes.